Novel process of bio-chemical ammonia removal from air streams using a water reflux system and zeolite as filter media. (February 2016) - Vitzthum von Eckstaedt, Sebastian; Charles, Wipa; Ho, Goen; Cord-Ruwisch, Ralf
Abstract: A novel biofilter that removes ammonia from air streams and converts it to nitrogen gas has been developed and operated continuously for 300 days. The ammonia from the incoming up-flow air stream is first absorbed into water and the carrier material, zeolite. A continuous gravity reflux of condensed water from the exit of the biofilter provides moisture for nitrifying bacteria to develop and convert dissolved ammonia (ammonium) to nitrite/nitrate. The down-flow of the condensed water reflux washes down nitrite/nitrate preventing ammonium and nitrite/nitrate accumulation at the top region of the biofilter. The evaporation caused by the inflow air leads to the accumulation of nitrite to extremely high concentrations in the bottom of the biofilter. The high nitrite concentrations favour the spontaneous chemical oxidation of ammonium by nitrite to nitrogen (N2 ). Tests showed that this chemical reaction was catalysed by the zeolite filter medium and allowed it to take place at room temperature. This study shows that ammonia can be removed from air streams and converted to N2 in a fully aerated single step biofilter. The process also overcomes the problem of microorganism-inhibition and resulted in zero leachate production. Highlights: Novel biofilter that removes ammonia from air streams and converts it to N2 . Novel combination of biological and chemical reaction to convert ammonia to N2 . Zeolite catalytic chemical reaction of ammonia and nitrite to nitrogen gas.